The characters of fairy tales in the children's book illustration: a dragon and a witch - Ingrida Korsakaitė (Knygotyra)
Illustrated folk tales and fairy tales by Lithuanian authors make a great and valuable part of children's books. Fantastic motifs and supernatural characters have inspired quite a few Lithuanian artists to depict them in graphics.